2016
DOI: 10.1002/macp.201500486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AlEt3and an External Donor on the Distribution of Active Sites According to Their Stereospecificity in Propylene Polymerization over TiCl4/MgCl2Catalysts with Different Titanium Content

Abstract: The data on content of individual fractions with different microtacticity for poly(propylene) (PP) samples produced over titanium–magnesium catalysts (TMCs) with composition TiCl4/MgCl2 and different titanium contents (0.1 and 3.5 wt%), as well as on the effects of pretreatment of these catalysts with triethylaluminum and addition of an external electron donor to the polymerization reaction on the content of these fractions are obtained using preparative temperature rising elution fractionation. The TMC with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
5
14
0
Order By: Relevance
“…Cat-1 with ultralow Ti content is used as a model catalyst that mainly contains isolated mononuclear Ti species. [18][19][20][21][22][23][24][26][27][28][29][30] Cat-2 with higher Ti content and more clustered Ti species is similar with those supported ZÀ N catalysts used in polyolefin industry. Therefore, the catalysts used here can be taken as models for the two extremes of Ti dispersion states.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Cat-1 with ultralow Ti content is used as a model catalyst that mainly contains isolated mononuclear Ti species. [18][19][20][21][22][23][24][26][27][28][29][30] Cat-2 with higher Ti content and more clustered Ti species is similar with those supported ZÀ N catalysts used in polyolefin industry. Therefore, the catalysts used here can be taken as models for the two extremes of Ti dispersion states.…”
Section: Introductionsupporting
confidence: 67%
“…Similar phenomena have been reported in previous literatures. [34][35][36] It can be found that the melting temperature (T m ) and melting enthalpy (ΔH m ) gradually increased with proceeding of the polymerization for both catalysts. However, the T m and ΔH m of PP catalyzed by Cat-1 were lower than those of PP catalyzed by Cat-2 under the same conditions.…”
Section: Activity and Polymer Chain Structurementioning
confidence: 98%
See 1 more Smart Citation
“…Stereospecificity of active sites depends on the additional surface compounds (aluminum alkyls or electron‐donating compounds) adsorbed on the neighboring metal ions in the second coordination sphere of active Ti ions. We have recently used this model for discussion of our results regarding the effect of organoaluminum cocatalyst and ED on the formation and distribution of fractions with different microtacticities for PP produced over the “donor‐free” TMC with very low titanium content at polymerization in the absence and presence of the ED …”
Section: Resultssupporting
confidence: 74%
“…We have recently used the p‐TREF technique to study the distribution of active centers according to stereospecificity in “donor‐free” TiCl 4 /MgCl 2 catalysts with different titanium contents . In case of the catalyst with a very low titanium content (0.1 wt % of Ti), a much higher amount of non‐stereoregular (“atactic”) fraction (65%) is formed compared to the regular supported catalyst containing (3.5 wt % of Ti 35% of the “atactic” fraction).…”
Section: Introductionmentioning
confidence: 99%